Improving The Progress Monitoring Task Of Agile Kanban Method: An Enhanced Theoretical Framework And Its Implication - Alaidaros, Hamzah; Omar, Mazni; Romli, Rohaida (International Journal of Scientific & Technology Research, 2020)
Several studies claimed that software project management (SPM) failed in realizing software projects due to inadequate progress monitoring. Indeed, the successful implementation of software projects relies entirely on effective monitoring approaches. Recently, the adoption of Agile Kanban method in SPM is continuously on the rise despite its shortcoming in its progress monitoring task. Therefore, this paper aims to enhance the theoretical framework for improving the progress monitoring task of Agile Kanban method and highlight its implication on SPM domain. To achieve this aim, an exploratory research design was employed to identify the problem, review the related literature, and to develop the enhanced framework. The findings confirm the highly need of improving the monitoring task of Agile Kanban method, which would assist project managers to effectively monitor the development process of software projects. Accordingly, the results of literature have been utilized to construct an enhanced theoretical framework, thus delivering software products on time within budget could be achieved. Practically, it is hoped that the framework can provide a guideline for developing models focus on improving the progress monitoring task.